Physicians' experience and opinion on contraindications to allergen immunotherapy: the CONSIT survey - Rio, Pablo Rodriguez del; Pfaar, Oliver (Annals of allergy, asthma and immunology, 2017)
Background Allergen immunotherapy (AIT) is the only disease-modifying treatment in allergy but several contraindications limit its use. Objective To collect the outcome of using AIT in theoretically contraindicated situations in real patients in the Contraindications to Specific ImmunoTherapy (CONSIT) survey. Methods The CONSIT is an electronic European Academy of Allergy and Clinical Immunology survey conducted to gather the safety outcomes of patients undergoing subcutaneous, sublingual, or venom AIT and the opinions of physicians on each of 17 selected conditions: children younger than 5 years; starting AIT during pregnancy; controlled severe asthma; arrhythmias; coronary disease; cancer; autoimmune disease; bone marrow and solid organ transplantation; human immunodeficiency virus and acquired immunodeficiency syndrome; previous anaphylaxis during AIT; use of β-blockers, angiotensin-converting inhibitors, cyclosporine, and methotrexate; and inability to communicate. Safety using AIT was reported in a 3-point scale: 1, “no problems”; 2, “minor problems” (requiring only dose modifications); and 3, “major problems” (AIT not tolerated). Each physician was asked about the degree of contraindication that each condition should have: no contraindication (score 1), relative contraindication (score 2), or absolute contraindication (score 3). Results Five hundred twenty physicians (75% Europeans, 89% allergists) reported on approximately 45,000 patients undergoing AIT with any of these conditions. Major problems were infrequent, occurring more frequently in patients with asthma (9.9%) and with previous anaphylaxis from AIT (9.5%). Regarding opinions, experienced physicians scored a significantly lower mean for all conditions than non-experienced physicians for all routes. Conclusion Major problems were infrequent and experienced physicians were less likely to be restrictive in the use of AIT.
Gesehen am 20.07.2018